Ayat-Ayat Kauniyah dan Qur’aniyah dalam Perspektif Epistemologi Ilmu - Mardatillah. B, Alya; Dewi, Eva; Anwar, Khairil (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This study aims to examine the relationship between Kauniyah and Qur’aniyah verses in constructing the epistemology of knowledge from an Islamic perspective. The research employs a literature review method, gathering data from various sources such as books, articles, journals, and relevant documents. The analysis reveals that Kauniyah verses encourage scientific exploration through observation and reasoning, while Qur’aniyah verses provide moral guidance and spiritual values. The integration of both forms a holistic, rational, and transcendental epistemological framework. The study concludes that the Qur'an, as the ultimate source of knowledge, emphasizes the harmony between revelation and science, advocating for a balanced approach that utilizes reason and observation to understand the universe while adhering to divine guidance. This integration fosters comprehensive knowledge aligned with Islamic teachings and serves the betterment of humanity.